Insurance denials for cancer clinical trial participation after the Affordable Care Act mandate. Issue 15 (23rd March 2017) - Mackay, Christine B.; Antonelli, Kaitlyn R.; Bruinooge, Suanna S.; Saint Onge, Jarron M.; Ellis, Shellie D.
Abstract : BACKGROUND: The Affordable Care Act (ACA) includes a mandate requiring most private health insurers to cover routine patient care costs for cancer clinical trial participation; however, the impact of this provision on cancer centers' efforts to accrue patients to clinical trials has not been well described. METHODS: First, members of cancer research centers and community‐based institutions (n = 252) were surveyed to assess the status of insurance denials, and then, a focused survey (n = 77) collected denial details. Univariate and multivariate analyses were used to examine associations between the receipt of denials and site characteristics. RESULTS: Overall, 62.7% of the initial survey respondents reported at least 1 insurance denial during 2014. Sites using a precertification process were 3.04 times more likely to experience denials (95% confidence interval, 1.55‐5.99; P  ≤ .001), and similar rates of denials were reported from sites located in states with preexisting clinical trial coverage laws versus states without them (82.3% vs 85.1%; χ2  = 50.7; P  ≤ .001). Among the focused survey sites, academic centers reported denials more often than community sites (71.4% vs 46.4%). The failure of plans to cover trial participation was cited as the most common reason provided for denials (n = 33 [80.5%]), with nearly 80% of sites (n = 61) not receiving a coverage response from the insurer within 72 hours. CONCLUSIONS: Despite the ACA's mandate for most insurers to cover routine care costs for cancer clinical trial participation, denials and delays continue. Denials may continue because some insurers remain exempt from the law, or they may signal an implementation failure. Delays in coverage may affect patient participation in trials. Additional efforts to eliminate this barrier will be needed to achieve federal initiatives to double the pace of cancer research over the next 5 years. Future work should assess the law's effectiveness at the patient level to inform these efforts. Cancer 2017;123:2893–900. © 2017 American Cancer Society . Abstract : Insurance denials for participation in adult cancer clinical trials continue despite the Affordable Care Act's clinical trial policy. Both academic and community research sites have experienced insurance denials and delays as barriers to patient enrollment.